INVERTIBILITY OF SOME SINGULAR INTEGRAL OPERATORS WITH SHIFT - Sargsyan, A.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
The paper studies some singular integral operators with the Carleman shift. Sufficient conditions ensuring the invertibility of these operators are obtained. The scheme for construction of an invertible operator is given.
Keywords: singular operator; shift